A practical alternative to calculating unmet need for family planning - Sinai I; Igras S; Lundgren R (Dove Medical Press, 2017)
Irit Sinai,1,2 Susan Igras,1 Rebecka Lundgren1 1Institute for Reproductive Health, Georgetown University, Washington, DC, USA; 2Palladium, Washington, DC, USA Abstract: The standard approach for measuring unmet need for family planning calculates actual, physiological unmet need and is useful for tracking changes at the population level. We propose to supplement it with an alternate approach that relies on individual perceptions and can improve program design and implementation. The proposed approach categorizes individuals by their perceived need for family planning: real met need (current users of a modern method), perceived met need (current users of a traditional method), real no need, perceived no need (those with a physiological need for family planning who perceive no need), and perceived unmet need (those who realize they have a need but do not use a method). We tested this approach using data from Mali (n=425) and Benin (n=1080). We found that traditional method use was significantly higher in Benin than in Mali, resulting in different perceptions of unmet need in the two countries. In Mali, perceived unmet need was much higher. In Benin, perceived unmet need was low because women believed (incorrectly) that they were protected from pregnancy. Perceived no need – women who believed that they could not become pregnant despite the fact that they were fecund and sexually active – was quite high in both countries. We posit that interventions that address perceptions of unmet need, in addition to physiological risk of pregnancy, will more likely be effective in changing behavior. The suggested approach for calculating unmet need supplements the standard calculations and is helpful for designing programs to better address women’s and men’s individual needs in diverse contexts. Keywords: unmet need, family planning, contraception, Mali, Benin